Studi Fenomena Penyalahgunaan Kartu Keluarga Sejahtera pada Keluarga Penerima Manfaat Program Keluarga Harapan - Rahayu Dewi; Siti Nurjannah; Maya Atri Komalasari (Prodi Sosiologi Universitas Mataram, 2022)
This study examines the phenomenon of misuse of Prosperous Family Cards (KKS) carried out by Family Beneficiaries of the Family Hope Program (KPM-PKH) in Babakan Village, Sandubaya District, Mataram City. This research aims to (1) find out the forms of abuse committed by KPM-PKH and (2) the motives behind KPM-PKH committing acts of abuse KKS. The study used Alfred Schutz's motive theory that focused on Because of Motive and In Order to Motive to analyze the motives of actors committing KKS abuse. The research method used is qualitative with a phenomenological approach to obtaining more in-depth data. The data collection techniques used are interviews, observations and documentation. The data analysis used is the Milles and Huberman model, namely by reducing data, presenting data and drawing conclusions or verification. The results of the study found that the form of KKS abuse carried out by KPM-PKH in Babakan Village was by practicing KKS pawns. In the practice of pawn KKS researchers found that there are two stages passed by KPM-PKH individuals, namely (1) negotiations and (2) transactions. The Reason for the Motives behind KPM's conduct of KKS pawn actions is (1) financial difficulties (2) ease of making transactions (3) environmental influences (4) monitoring and prevention efforts that are less than optimal (5) unequivocal sanctions. While In Order to Motive the actors doing KKS pawns are (1) obtaining money loans (2) meeting unexpected and urgent needs (3) obtaining loans faster.